POLITENESS MAXIM FOUND IN THE CHARACTERS’ CONVERSATION IN RAYA AND THE LAST DRAGON MOVIE (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
This research is focused on the politeness expression performed by the characters in the movie. It aims at identifying the types of politeness maxim used in the conversation between characters in the movie. The research also analyses the speech function of politeness maxim occurred in the conversation between the characters. It applied observation method in collecting the data.Descriptive qualitative was utilized in analyzing the politeness maxim by elaborating each type of them. It used the theory from Leech (1983) was used to analyze it. The data were taken from the new released Disney Movie, Raya and the Last Dragon (2021). In addition, the speech functions were also examined using the theory proposed by Holmes (2013) to find out clear explanation on which speech function categorized from the utterances. The research concluded that there were politeness maxim used in the conversation of the characters in the movie and they have different speech function in order to deliver speaker’s intention.